An Overview of Pharmaceutical Care in Type II Diabetes Mellitus Patients: Current Position and Prospects - Theivasigamani, Kumutha; Palaniappan, Senthilkumar (Current Diabetes Reviews, 2024)
Diabetes mellitus is an ongoing disease that is related to a high mortality rate due to severe complications. Diabetes mellitus type 2 (DMT2) is a persistent metabolic deficiency and its prevalence has been increasing consistently worldwide. As a result, it is rapidly turning into a plague in some parts of the world, and the number of people affected is expected to double in the following decade due to an increase in the maturing populace, adding to the overall existing importance for medical service providers, particularly in the underdeveloped nations. Extensive diabetes care is an intricate task that takes a whole group of medical care experts, including drug specialists, to provide multidisciplinary care for the patients. The duty of drug experts has changed significantly in recent years, changing from conventional drug dispensing in the drug store to patient- centered clinical support services. Upgrading the medication treatment to accomplish better remedial results without causing drug-related issues has been considered the essential objective of treatment for diabetic patients. This review discusses the healthcare needs of patients with T2DM, the current evidence for the role of pharmacists in diabetes care, and insight into the upcoming role of pharmacists in its management. The advanced role of clinical pharmacists in diabetes control through drug treatment, diabetes care centers, and diabetes health counselor schooling, is also discussed in this review.
Keywords: pharmaceutical care